2022
DOI: 10.3389/fenvs.2022.957204
|View full text |Cite
|
Sign up to set email alerts
|

Promoting systems thinking and pro-environmental policy support through serious games

Abstract: We evaluated whether teaching the public about the “critical zone”–the Earth’s outer skin, critical to all life—via a digital serious game can affect adults’ systems thinking about the environment and support policies to protect the environment. An experiment (N = 152) compared the effects of playing “CZ Investigator” versus viewing a static website on systems thinking about the Food-Energy-Water (FEW) nexus and support for relevant public policies. The serious game had the strongest effects on our outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In a similar vein, our sample size was rather small, so that possible moderating variables for the effect of the VR intervention on environmental awareness could not be assessed. For example, Sajjadi et al (2022) found that serious games about system thinking had the strongest effects on pro-environmental attitudes for those participants with less past science education. Future studies should take such variables into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, our sample size was rather small, so that possible moderating variables for the effect of the VR intervention on environmental awareness could not be assessed. For example, Sajjadi et al (2022) found that serious games about system thinking had the strongest effects on pro-environmental attitudes for those participants with less past science education. Future studies should take such variables into account.…”
Section: Discussionmentioning
confidence: 99%
“…Lezak and Thibodeau (2016) were able to show that systems thinkers tend to support policies on climate change. Sajjadi et al (2022) could show that a learning experience can increase systems thinking and that systems thinking in turn leads to policy support regarding measures concerning foodenergy-water nexus. The authors have developed an interesting method to indirectly measure system thinking by assessing different scenarios and their impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has already shown that VR might be an effective tool to raise awareness and subsequently increase the pro-environmental behavioral intention of users (Ahn et al, 2015), particularly for those with less science education (Sajjadi et al, 2022). However, despite the increasing popularity of VR technology, the pervasiveness of immersive VR devices (Head-mounted Displays—HMDs) in the United States is still relatively low, at only 15% of the households in the population (Kolmar, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, although we have message conditions in our experimental design that present both cancer risks and screening rates information, we did not explicitly specify a link between these two components (that higher screening rates are associated with lower national risks of dying from cancer). As the actual cancer risks are lower than what people estimated, specifying that the level of risk is due in part to the high prevalence of cancer screening may encourage people to think about the issue more holistically to better understand the causal mechanisms (known as systems thinking, Arnold & Wade, 2015; Sajjadi et al., 2022). In this situation, screening intention may increase even if people know that the risks are lower than what they expected, though this assumption should be tested in future research.…”
Section: Limitationsmentioning
confidence: 99%